Analisis Pengaruh Faktor Sosial Ekonomi terhadap Kepatuhan Pasien dalam Penggunaan Antibiotika Secara Oral di Puskesmas X Kota Depok: Analysis Of The Impact Of Socio-Economic Factors On Patient Compliance In The Use Of Oral Antibiotics At Community Health Centers X Depok City - Agnes Tri Ningsih; Eka Pebi Hartianty (Jurnal Farmasi dan Farmakoinformatika, 2026)
The inappropriate use of antibiotics is one of the main factors contributing to antimicrobial resistance (AMR), which significantly increases global morbidity and mortality rates. Patient adherence to antibiotic regimens plays a crucial role in preventing the development of resistance. Socioeconomic factors, such as educational level, occupation, and income, are suspected to influence adherence levels. This study aims to analyze the impact of socioeconomic factors on adherence to oral antibiotic use at Puskesmas X in Depok City. The results indicate that socioeconomic factors (education, occupation, and income) collectively have a significant effect on adherence to oral antibiotic use, contributing 10.8% to the variance in adherence, while the remaining 89.2% is influenced by other unexamined factors. An ANOVA (F-test) yielded a significance value of 0.011 (< 0.05), thereby supporting the general hypothesis (H1). Further analysis using partial t-tests revealed that educational level was the most influential factor, with a significance value of 0.052, close to the α threshold of 0.05. This finding suggests that higher educational attainment enhances individuals’ ability to understand medical information and follow antibiotic usage instructions, thereby improving adherence. Conversely, occupation (α = 0.759) and income level (α = 0.122) did not demonstrate a significant influence on adherence to oral antibiotic use